Shapers of urban form explorations in morphological agency - Larkham, P. J. (Peter J.) 1960-; Lilley, Keith D. (New York, NY Routledge, 2014)
"People have designed cities long before there were urban designers. In Shapers of Urban Form, Peter Larkham and Michael Conzen have commissioned new scholarship on the forces, people, and institutions that have shaped cities from the Middle Ages to the present day. Larkham and Conzen collect new essays in "urban morphology," the people-centered predecessor to contemporary theories of top-down urban design. Shapers of Urban Form focuses on the social processes that create patterns of urban forms in four discrete periods: Pre-modern, early modern, industrial-era and postmodern development. Featuring studies of English, American, Western and Eastern European, and New Zealand urban history and urban form, this collection is invaluable to scholars of urban design and town planning, as well as urban and economic historians"-- Provided by publisher.
Foreword / Ivor Samuels -- Part I. Introduction : Agents, agency, and urban form: "The making of the urban landscape" / Peter J. Larkham and Michael P. Conzen -- Part II. Agency in pre-modern settings : Royal authority and urban formation: King Edward I and the making of his 'new towns' / Keith D. Lilley -- Ecclesiastical authorities and the form of medieval towns / Terry R. Slater -- Urban corporate governance and the shaping of medieval towns / Anngret Simms -- Part III. Agency in early modern settings : Absolute decisions: towns fit for a king / Katharine Arntz Thomas -- Haussmann: reconsidering his role in the transformation of Paris / Michaël Darin -- Colonial regime change and urban form: how Russian Novo-Arkhangel'sk became American Sitka / Michael P. Conzen -- Part IV. Agency in industrial-era settings : Squeezing railways into cities: creating variable solutions in Britain and the United States, 1820-1900 / Arthur J. Krim -- Shaping the housing of industrialists and workers: the textile settlements of Księży Młyn (Łódź) and Żyrardów in Poland / Marek Koter and Mariusz Kulesza -- Residential differentiation in nineteenth-century Glasgow: a morphogenetic study of Pollokshields garden suburb / Michael Pacione -- The imprint of the owner-builder on American suburbs / Richard Harris -- Part V. Agency in late modern and postmodern settings : Modernism against history: understanding building typology and urban morphology among Italian architects in the twentieth century / Nicola Marzot -- A new vision: the role of municipal authorities and planners in replanning Britain after the Second World War / Peter J. Larkham -- In search of new syntheses: urban form, late flowering modernism, and the making of megastructural Cumbernauld / John R. Gold -- Morphological processes, planning and market realities: reshaping the urban waterfront in Auckland and Wellington / Kai Gu -- 'Birmingham needs you. You need Birmingham': cities as actors and actors in cities / Timothy Hall and Phil Hubbard -- Part VI. Envoi : Agents and agency, learning, and emergence in the built environment: a theoretical excursion / Karl Kropf.
Includes bibliographical references and index.
Keywords: Urbanization -- History